DESIGN OF ACCOUNTING INFORMATION SYSTEM AT SEVENTH-DAY ADVENTIST CHURCH TAMAN HARAPAN CONGREGATION RAP-RAP AIRMADIDI - Ika Prayanthi; Meily Yoke Betsy Kalalo; Herman Karamoy (ACCOUNTABILITY, 2023)
The Seventh-day Adventist Church of Taman Harapan Rap-Rap congregation must design an accounting information system mechanism. This study aims to develop accounting information system mechanisms. This research used the case study method to evaluate congregational financial management practices and the modified waterfall method for creating accounting information system mechanisms. The congregation has not fulfilled most of the implementation of an effective accounting information system, so urgent improvements are needed. Accounting information systems are designed based on accounting information systems tailored to user needs. To improve the quality of accounting information systems, researchers also designed templates in Microsoft Excel to facilitate recording and providing congregational financial statements. With the new system, the resulting financial statements are expected to be more accurate, available when needed, and reliable.